Influence of Audiovisual Stimuli on Emotions and Sustainable Consumptions Behavior: A Study of Young People in an Emerging Economy - Amado Mateus, Marelby; Guzman Rincon, Alfredo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The study explores strategies to effectively promote sustainable products to Generation Z by examining the emotional impact of audiovisual stimuli. Through a mixed-methods approach, FaceReader software captured microexpressions, while open-ended questionnaires provided qualitative insights. Results indicate a predominance of neutral emotions, with notable variations in happiness and sadness, and a polarization between environmental concern and optimism for change. Findings highlight the importance of emotional engagement in shaping sustainable behaviors. The research enhances understanding of sustainable consumption in emerging economies, offering valuable insights for marketers aiming to connect with environmentally conscious young consumers.